STUDI FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN PELANGGAN DALAM MENINGKATKAN KERJASAMA BERKELANJUTAN (STUDI PADA CV MITRA KASIH PERKASA) - Perkasa KS, Nicholas Anggada; Soesanto, Harry; Sukresna, I Made (Master of Management Diponegoro University, 2016)
The purpose of this research is to test the influences of product quality, after sales service, and direct marketing oncustomer trustto impact sustainability relationship. Using these variables, the usage of these variables are able to solve the arising problem within customersCV. Mitra Kasih Perkasa. Statement of this problem is how increase sustainability relationship?.The samples size of this research is105customersCV. Mitra Kasih Perkasa. Using the Structural Equation Modeling (SEM). The results show that product quality, after sales service, and direct marketing oncustomer trustto impact sustainability relationship.The effect of core product quality on customer trustare significant;The effect after sales service on customer trustare significant;The effect of direct marketing on customer trustare significant;The effect customer truston sustainability relationship are significant; and The effect direct marketing on sustainability relationship are significant.